Formação de professores de matemática: expectativas e práticas pedagógicas sobre ensino e aprendizagem de estudantes com deficiência visual - Veregue, Geisa (Universidade Federal de São Carlos, 2023)
This research has the general objective of developing, applying and evaluating a collaborative training program, with a view to the performance of mathematics teachers with students with visual impairment. The specific objectives are: (a) to characterize the pedagogical practices of Mathematics teachers who work in the Final Years of Elementary School; (b) describe the perception of teachers about teaching mathematics to visually impaired students, before and after in-service training. Under a qualitative approach, the study is characterized as a collaborative research. Study participants were three teachers of the Mathematics curricular discipline, working in the Final Years of Elementary School, and a teacher from the resource room for students with visual impairments. The research was carried out in a state public school, in a city in the interior of the state of São Paulo. Data collection and analysis procedures were organized into five stages: characterization of teachers, pedagogical practice, survey of information regarding pedagogical practice, in-service training planning, aplication of training and evaluation of training. The instruments used in the research were: categorization questionnaire; semi-structured interview scripts; fiel journal; collaborative training evaluation script. The collected data were analyzed and organized using the categorical contente analysis technique. The results indicate that in-service training for mathematics teachers provided significant exchanges and reflections between them, favoring accessibility of curricular contentes for students with visual impairments, and this was possible because training was carried out during working hours, based on cases actual students. The study showed the importance of didactic resources and strategies, as important aspects for the success of teaching mathematics for the Middle School in the perspective of school inclusion.
Mathematics teacher training: expectations and pedagogical practices on teaching and learning for visually impaired students
Keywords: Educação especial; Formação de professores; Deficiência visual; Matemática; Special education; Teacher training; Visual impairment; Mathematics; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO